Polycaprolactone/starch composite: Fabrication, structure, properties, and applications - Ghavimi, S.A.A.; Ebrahimzadeh, M.H.; Solati-Hashjin, M.; Abu Osman, Noor Azuan (Wiley Black, 2015)
Interests in the use of biodegradable polymers as biomaterials have grown. Among the different polymeric composites currently available, the blend of starch and polycaprolactone (PCL) has received the most attention since the 1980s. Novamont is the first company that manufactured a PCL/starch (SPCL) composite under the trademark Mater-Bi (R). The properties of PCL (a synthetic, hydrophobic, flexible, expensive polymer with a low degradation rate) and starch (a natural, hydrophilic, stiff, abundant polymer with a high degradation rate) blends are interesting because of the composite components have completely different structures and characteristics. PCL can adjust humidity sensitivity of starch as a biomaterial; while starch can enhance the low biodegradation rate of PCL. Thus, by appropriate blending, SPCL can overcome important limitations of both PCL and starch components and promote controllable behavior in terms of mechanical properties and degradation which make it suitable for many biomedical applications. This article reviewed the different fabrication and modification methods of the SPCL composite; different properties such as structural, physical, and chemical as well as degradation behavior; and different applications as biomaterials. (c) 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2482-2498, 2015.